Phylogenetic analysis of Phloeidae Amyot & Serville, 1843 (Hemiptera: Heteroptera: Pentatomomorpha: Pentatomoidea) and its position in the superfamily Pentatomoidea, based on morphological studies - Lopez, Guilherme Enrique Luisi (2024)
The family Phloeidae, a.k.a. Neotropical bark bugs, is one of the less speciose families of Pentatomoidea, with three species included in two genera, Phloea Spinola and Phloeophana Kirkaldy. Distributed in the Neotropics, these bugs are recognized by the large size, flattened body, presence of foliaceous expansions throughout the body, eyes divided into dorsal and ventral portions, and cryptic coloration, camouflaging themselves in the barks of the trees. Despite their larger size, the identity of the three species is not well delimited, their distribution is sparsely known, and their relationships with other Pentatomoidea families is still unknown. Besides that, some authors debate wether the enigmatic genus Serbana Distant, described from Borneo, should be included in Phloeidae or not. In this dissertation, we present a morphological review of the family Phloeidae in the Neotropics (considering Phloea and Phloeophana), providing new diagnoses for the family, genera and species, an identification key for adults and nymphs of the three species, and describing chromatic variation in Phloea subquadrata Spinola. We also review the literature and present synonymic lists and updated distribution maps, including unpublished data from collection specimens and citizen science platforms. We also performed a phylogenetic analysis using a morphological approach to investigate two main questions: the relationships between Phloeidae and the other pentatomoids, and wether Serbana is included in Phloeidae or not. A morphological matrix with 123 revised characters was assembled, and 71 species in 12 families were included in our analyses. Photographic documentation is provided for most of the morphological characters. Our results corroborated that Serbana should be included in Phloeidae, as sister group to Phloea + Phloeophana. The three genera share many synapomorphies, which are discussed in this study. Our results are dubious regarding the phylogenetic relationships of the Phloeidae (including Serbana), suggesting two distinct hypotheses: a sister group relationship between Phloeidae and Scutelleridae, or Phloeidae as sister group of a large clade including Scuteleridae and other four Pentatomoidea families. Finally, we briefly discuss the incongruence between our morphological data and recent molecular evidence supporting Serbana as part of the Pentatomidae, and possible morphological convergences as a possible explanation for the incongruences we found.